In vitro morphogenic response in cotyledon explants of semecarpus anacardium L. - Panda, Bhuban Mohan; Hazra, Sulekha (Plant Biotechnology Reports, 2012)
Three different morphogenic responses-caulogenesis, direct somatic embryogenesis, and callusing-were noted in cotyledon explants of Semecarpus anacardium L. cultured in woody plant medium (WPM) containing thidiazuron (TDZ). Thidiazuron, at all concentrations tested, induced organogenic as well as embryogenic responses. The organogenic buds differentiated to shoots and the embryogenic mass (EM) gave rise to globular embryos which differentiated up to cotyledon-stage embryos on repeated culture in growth regulator (GR)-free WPM medium containing 0.2% activated charcoal after the removal of TDZ. The organogenic and embryogenic responses were optimal in 9.08 mu M TDZ after the removal of TDZ. Elongated shoots rooted in half-strength liquid WPM medium with 2.46 mu M indole butyric acid. Plants were successfully acclimatized and transferred to soil. Histological studies confirmed the direct origin of the organogenic buds from the cotyledon explants. The EMs produced somatic embryos on repeated culture in charcoal incorporated GR-free medium. Morphogenic callus formation from the cotyledon explants was also noted. This callus on repeated culture in WPM medium with charcoal differentiated into somatic embryos. Repetitive somatic embryogenesis was evident from direct and indirectly formed primary embryos. The somatic embryos did not convert into plantlets, though sporadic germination of embryos was observed through the emergence of roots.
Keywords: callus; Caulogenesis; Globular embryos; Growth regulator; Histology; somatic embryogenesis